The Inoculation Effect of Arbuscular Mycorrhizal Fungi (AMF) and Phosphate Fertilization to Increase Cherry Tomato Production - Cahyani, Ardhia Dwi; Lukiwati, Dwi Retno; Fuskhah, Eny (Journal of Tropical Crop Science and Technology, 2020)
One of phosphate (P) fertilizer i.e. SP-36 is expensive and can be obtained by rock phosphate (RP). Rock phosphate combined with Vesicular Arbuscular Mycorrhizal fungus (VAM) could increase Pavailability. VAM consists of many species, so it is necessary to test the role of VAM species on cherry tomato plant. This study aims to examine the effect of VAM species and phosphate fertilization to improve cherry tomato production. The research use a Completely Randomized Design (CRD) which consisted of two factors with three replications. The first factor is the phosphate fertilization (P0= without P fertilizer, P1= SP-36, P2= rock phosphate) and the second factor is VAM species (M0= control without mycorrhizae, M1= Glomus etunicatum, M2= Glomus fasciculatum, M3= double inoculation of G. etunicatum and G. fasciculatum). The results show that mycorrhizae inoculation increases plant height, fruit number, fruit weight and accelerates flowering age compared to without inoculation. BP fertilization increases fruit weight. BP+CMA produces number of fruit equivalent to SP-36+CMA. BP+G. etunicatum treatment significantly increases fruit weight compared to SP-36+G. etunicatum. G. etunicatum inoculation gives the highest fruit weight compared to other inoculation.